Impact of a stress coping strategy on perceived stress levels and performance during a simulated cardiopulmonary resuscitation: A randomized controlled trial - Hunziker, Sabina; Pagani, Simona; Fasler, Katrin; Tschan, Franziska; Semmer, Norbert K.; Marsch, Stephan U. (My University, 2013)
Abstract Background: Cardiopulmonary resuscitation (CPR) causes significant stress, which may cause deficiencies in attention and increase distractibility. This may lead to misjudgements of priorities and delays in CPR performance, which may further increase mental stress (vicious cycle). This study assessed the impact of a task- focusing strategy on perceived stress levels and performance during a simulated CPR scenario. Methods: This prospective, randomized-controlled trial was conducted at the simulator-center of the University Hospital Basel, Switzerland. A total of 124 volunteer medical students were randomized to receive instructions about focusing on relevant task elements by posing two task-focusing questions (“what is the patient’s condition?”, “what immediate action is needed?”) when feeling overwhelmed by stress (intervention-group) or a control-group. The primary outcome was the perceived levels of stress and feeling overwhelmed (stress/overload); secondary outcomes were hands-on time, time to start CPR and number of leadership statements. Results: Participants in the intervention-group reported significantly less stress/overload levels compared to the control-group (mean difference: -0.6 (95%CI - 1.3, -0.1), p=0.04). Higher stress/overload was associated with less hands-on time. Leadership statements did not differ between groups, but the number of leadership statements did relate to performance. Hands-on time was higher in the intervention-group, but the difference was not statistically different (difference 5.5 (95%CI -3.1, 14.2), p=0.2); there were no differences in time to start CPR (difference -1.4 (95%CI - 8.4, 5.7), p=0.71). Conclusions: A brief task-focusing strategy decreased perceived stress without significantly affecting performance in a simulated CPR. Further studies should investigate more intense interventions for reducing stress.